1999
DOI: 10.1159/000018265
|View full text |Cite
|
Sign up to set email alerts
|

Spindle Cell Hemangioma

Abstract: A 27-year-old woman presented with multiple nodules closely grouped on her right upper distal extremity. The lesions, dating from childhood, increased slowly in time. Microscopic examination of one nodule showed the histologic features of spindle cell hemangioendothelioma (SCH). At the periphery of the nodule there were also some features of the so-called sinusoidal hemangioma. Clinically, SCH can present as a solitary lesion or as multiple lesions in zonal distribution. When the lesions are multiple, the diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 16 publications
(23 reference statements)
0
16
1
Order By: Relevance
“…Individual lesions are asymptomatic or painful, smooth‐surfaced, skin‐colored to bluish, firm nodules, and show the potential for local or regional recurrence and multifocal slow growth 7,16 . SCH shows histopathologic features of dermal or subcutaneous nodules composed of thin‐walled dilated vascular structures containing inconsistently organized thrombi and phleboliths in their lumina, and more solid, cellular zones with fascicles of spindle cells of bland, mitotically inactive cells with tapering or rounded vesicular nuclei, admixed with small aggregates of plump, epithelioid cells, some of which with intracytoplasmic vacuoles 5,7 . Immunohistochemically, endothelial cells lining vascular spaces and epithelioid cells are positive for factor‐VIII‐related antigen, CD31, CD34, and Ulex europaeus I lectin, whereas the spindle cells are negative for these markers 5,16 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Individual lesions are asymptomatic or painful, smooth‐surfaced, skin‐colored to bluish, firm nodules, and show the potential for local or regional recurrence and multifocal slow growth 7,16 . SCH shows histopathologic features of dermal or subcutaneous nodules composed of thin‐walled dilated vascular structures containing inconsistently organized thrombi and phleboliths in their lumina, and more solid, cellular zones with fascicles of spindle cells of bland, mitotically inactive cells with tapering or rounded vesicular nuclei, admixed with small aggregates of plump, epithelioid cells, some of which with intracytoplasmic vacuoles 5,7 . Immunohistochemically, endothelial cells lining vascular spaces and epithelioid cells are positive for factor‐VIII‐related antigen, CD31, CD34, and Ulex europaeus I lectin, whereas the spindle cells are negative for these markers 5,16 …”
Section: Discussionmentioning
confidence: 99%
“…Although SCH initially presents as a distinctive low‐grade variant of angiosarcoma and can be classified into vascular tumors of intermediate or low‐grade malignant potential, it has been suggested that spindle cell hemangioendothelioma may be a non‐neoplastic, reactive process arising in association with a local congenital or acquired vascular malformation 4,7,16–18 . SCH can be associated with epithelioid hemangioendothelioma, congenital lymphedema, Maffucci's syndrome, Klippel–Trénaunay syndrome, early onset varicosities, Kasabach–Merritt syndrome, and arteriovenous fistula 4–7,19–21 . As we had evaluated bony abnormalities of our patient using MRI, possibility of Maffucci's syndrome can be ruled out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of neoplasms display intravascular proliferations [10, 11, 20, 21, 22, 23, 24, 25, 26, 27]. These include reactive angioendotheliomatosis, benign intravascular endothelial hyperplasia, angiosarcoma and retiform hemangioendothelioma.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Clinically, the lesions may occur solitary or multiple in zonal distribution. Most frequently, the single lesions are small, usually 0.5 to 2.0 cm, asymptomatic, bluish nodules with a livedoid pattern and of a firm consistence 1,3,6 . A case of multiple SCH extending over the entire body was described by Fletcher et al 7 Cases of multiple lesions have been diagnosed in association with Maffucci's syndrome 8,9 .…”
Section: Discussionmentioning
confidence: 99%